1993
DOI: 10.1002/jsfa.2740620414
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of single and mixed culture fermentation of pito beer

Abstract: Abstract:The fermentation of Pito, a traditional alcoholic beverage, was done using selected yeast strains or a crude mixed yeast culture collected from traditional breweries and two types of sorghum malt. The fermentation characteristics and product quality of the pure and mixed fermentations were monitored and compared. Significant differences were observed between the mixed culture fermentation and the single culture fermentations. Acid production of the mixed culture fermentations was higher whereas ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 11 publications
2
27
0
Order By: Relevance
“…Changing trends of flavours was helpful to monitor the process of fermentation; in addition, of interest were their rapid variations during the whole fermentation process. It was known that beer flavours were produced by the metabolism of yeasts (Bvochora & Zvauya, 2001;De Stefano & Montanari, 1996;Demuyakor & Ohta, 1993;Vanderhaegen, Delvaux, Daenen, Verachtert, & Delvaux, 2007). The rapid increase of four flavour compounds at the beginning of fermentation demonstrated that metabolism of yeasts was robust and malt juice was immediately utilised (Guido et al, 2004;Petersen et al, 2004;Zaldivar, Martinez, & Ingram, 1999).…”
Section: Real-time Analysis Of Four Flavour Compoundsmentioning
confidence: 97%
“…Changing trends of flavours was helpful to monitor the process of fermentation; in addition, of interest were their rapid variations during the whole fermentation process. It was known that beer flavours were produced by the metabolism of yeasts (Bvochora & Zvauya, 2001;De Stefano & Montanari, 1996;Demuyakor & Ohta, 1993;Vanderhaegen, Delvaux, Daenen, Verachtert, & Delvaux, 2007). The rapid increase of four flavour compounds at the beginning of fermentation demonstrated that metabolism of yeasts was robust and malt juice was immediately utilised (Guido et al, 2004;Petersen et al, 2004;Zaldivar, Martinez, & Ingram, 1999).…”
Section: Real-time Analysis Of Four Flavour Compoundsmentioning
confidence: 97%
“…To avoid changes in product characteristics during scientific improvements of traditional food processes, it is important to understand the processes and formulation of the product (Demuyakor and Ohta, 1993). Some limited information is available on the fermentation (Bacha, 1997) and microbial load (Ashenafi and Mehari, 1995) of borde in central and southern Ethiopia respectively.…”
Section: Introductionmentioning
confidence: 99%
“…If allowed to ferment longer, the beer becomes progressively sourer in taste. The mieroorganisms responsible for souring have not been identified, but in view of the ambient fermentation temperature (27 -32°C) [76] and the aromatie character of the beer [79] theyare presumably heterofermentative lactic acid bacteria.…”
Section: Traditional Clear Beersmentioning
confidence: 99%
“…They are characterized by being filtered, but are somewhat doudy, sweetish and generally slightly sour tasting, of fruity aroma and contain 1-5 vol. % alcohol [69,77,79]. Brewing of these beers is a small-scale commercial enterprise [69,76].…”
Section: Traditional Clear Beersmentioning
confidence: 99%
See 1 more Smart Citation